1982
DOI: 10.1159/000233099
|View full text |Cite
|
Sign up to set email alerts
|

Role of C4-Binding Protein in the Defective Lysis of Sensitized Sheep Erythrocytes by Mouse Complement

Abstract: Passage of mouse EDTA-plasma over an anti-C4-binding protein (anti-C4-bp) affinity column reduced the C4-bp level by an average of 34% and increased the classical C pathway activity as measured with sensitized normal and desialylated sheep erythrocytes, but not versus sensitized rabbit erythrocytes. This suggests that C-regulation by C4-bp is independent of membrane sialic acid and provides evidence for the presence of a hitherto unknown preferential site for mouse C4-bp on sheep erythrocytes. The absence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although it is known that sialic acid acts as a receptor site for factor H [28,291, to our knowledge no information is available in this respect for C4bp. Indirect evidence has been presented against a role for sialic acid in the binding of mouse C4bp [30]. However, in a preliminary study we observed that the neuraminidase treatment of IgE (DES) enhanced the formation of the classical pathway C3 convertase.…”
Section: Discussionmentioning
confidence: 91%
“…Although it is known that sialic acid acts as a receptor site for factor H [28,291, to our knowledge no information is available in this respect for C4bp. Indirect evidence has been presented against a role for sialic acid in the binding of mouse C4bp [30]. However, in a preliminary study we observed that the neuraminidase treatment of IgE (DES) enhanced the formation of the classical pathway C3 convertase.…”
Section: Discussionmentioning
confidence: 91%